Banking sector credit and economic growth in Nigeria: An empirical investigation - Aniekan O. Akpansung; Sikiru Jimoh Babalola (CBN Journal of Applied Statistics, 2011)
The paper examines the relationship between banking sector credit and economic growth in Nigeria over the period 1970-2008. The causal links between the pairs of variables of interest were established using Granger causality test while a Two-Stage Least Squares (TSLS) estimation technique was used for the regression models. The results of Granger causality test show evidence of unidirectional causal relationship from GDP to private sector credit (PSC) and from industrial production index (IND) to GDP Estimated regression models indicate that private sector credit impacts positively on economic growth over the period of coverage in this study. However, lending (interest) rate impedes economic growth. Over and above, the paper recommends the need for more financial market development that favours more credit to the private sector with minimal interest rate to stimulate economic growth.
Keywords: C01; C32; O16; G17; G21; G28; 330; Bank credit; Economic Growth; Two-Stage Least Squares (TSLS)